Compared With a Nasointestinal Route, Pre-operative Enteral Nutrition via a Nasogastric Tube Reduced the Incidence of Acalculous Acute Cholecystitis After Definitive Surgery for Small Intestinal Fistula - Yao, Zheng; Tian, Weiliang; Xu, Xin; Zhao, Risheng; Zhao, Yunzhao (Frontiers in Medicine, 2021)
Purpose: This study aimed to investigate the difference in the efficacy of preoperative enteral nutrition (EN) via a nasogastric tube (NGT) and preoperative EN via a nasointestinal tube (NIT) in reducing the incidence of postoperative acalculous acute cholecystitis (AAC) after definitive surgery (DS) for small intestinal fistulas. Methods: Patients with a small intestinal fistula, who had a DS for the disease between January 2015 and March 2021, were enrolled in this study. They were divided into the NIT group and the NGT group based on the preoperative routes of feeding they received. The clinical characteristics of the two groups were analyzed, and the incidences of postoperative AAC in the two groups were evaluated. Results: A total of 200 patients were enrolled in the study, 85 in the NGT group and 115 in the NIT group. Thirty-one patients developed postoperative AAC (8 in the NGT group and 23 in the NIT group). The incidence of postoperative AAC was 15.5%. EN via the NGT route was associated with a reduction in the incidence of postoperative AAC (adjusted HR = 0.359; 95% CI: 0.139-0.931; P = 0.035). Conclusion: Preoperative EN via the NGT may reduce the incidence of postoperative AAC in patients who received a DS for small intestinal fistulas.